Best Friend Influence Over Adolescent Problem Behaviors: Socialized by the Satisfied. Issue 5 (3rd September 2017) - Hiatt, Cody; Laursen, Brett; Stattin, Håkan; Kerr, Margaret
Abstract : The present study was designed to examine best friend influence over alcohol intoxication and truancy as a function of relative perceptions of friendship satisfaction. The participants were 700 adolescents (306 boys, 394 girls) who were involved in same-sex best friendships that were stable from one academic year to the next. Participants completed self-report measures of alcohol intoxication frequency and truancy at 1-year intervals. Each member of each friendship dyad also rated his or her satisfaction with the relationship. At the outset, participants were in secondary school (approximately 13–14 years old) or high school (approximately 16–17 years old). More satisfied friends had greater influence than less satisfied friends over changes in intoxication frequency and truancy. Problem behaviors of less satisfied friends increased over time if the more satisfied friend reported relatively higher, but not relatively lower, initial levels of drinking or truancy. The results support the hypothesis that adolescent friends are not similarly influential. The power to socialize, for better and for worse, rests with the partner who has a more positive perception of the relationship.